Nova música para saxofone no Brasil: dialogismo no repertório de concerto - Paulo Sérgio Rosa Filho (2020)
Taking as a reference my previous experience as a performer, I was able to observe, within the Brazilian repertoire for saxophone, compositional elements that were presented in a recurring way in several works. Starting from the possibility that such recurrence could be analyzed in order to propose relationships between the history of the saxophone, its development, the traditional repertoire and the contemporary Brazilian repertoire, I took as a theoretical reference the thought of the Russian author Mikhail Bakhtin, in order to expose, from concepts such as dialogism, such as the saxophone and its repertoire, they can be permeated by an extra musical dimension. For this, I chose to focus on the solo saxophone repertoire, which was raised in three stages: by searching on my personal collection; by consulting the library of the UFMG School of Music; and, finally, through a questionnaire sent to 28 saxophone teachers in higher education. Once the survey was carried out, we selected the works for analysis taking into account two factors: the recurrence of the works' citation in the questionnaire responses and the diversity of materials and compositional techniques used. From the selected works, it was possible to present, in each particular case, how the compositional process relates to issues external to the musical text. Finally, I bring reflections on two of my works, composed during the course of the master's degree, in order to describe, this time from the perspective of the composer, composing as a process constantly pervaded by several statements in the tangle of dialogue.